Directory of journalists in continuing education programs of the Philippine Press Institute, 1986-90. (Philippine Press Institute, 1990)
Aimed at providing the general public and all concerned with a list of bona- fide Filipino journalists. the list includes newspaper men and women from all over the Philippines who have attended the seminars and workshops conducted by the Philippine Press Institute. The directory provides information on their present position and work, workshops and seminars attended former jobs, educational background, and date and place of birth.